The Synergy of Competency Strategy of Islamic Education Teacher to Improve the Quality of Education and Character of Students in Millenial Era - Yoespie Amirullah (Prodi Pendidikan Agama Islam, Fakultas Tarbiyah, Universitas Darussalam Gontor, 2020)
This article aims to form